Effect of Adding Nano Size Silica on Setting Time and Porosity of Mineral Trioxide Aggregate - Rouhani, Armita; Azimi, Niloofar; Akbari, Majid; Ahmadpour, Ali; Ashrafpour, Ehsan (Iranian Endodontic Journal, 2019)
Introduction: The aim of this study was to evaluate the effect of addition of nano-silica (SiO2) to mineral trioxide aggregate (MTA) on its setting time and porosity. Methods and Materials: The concentration 8% of nano-silica were prepared and added to the MTA powder. After mixing with water the setting time and porosity were evaluated and compared with pure MTA. Statistical analysis was performed using the t-test. The level of significance was set at 0.001. Results: The mean setting time of MTA+8% nano-silica (9.8±0.78) was significantly lower than MTA (23.3±2.16) (P<0.001). Also the mean porosity by imbibition method in MTA+8% nano-silica (23.49±0.48) was significantly higher than MTA (15.69±2.10) (P<0.001). There was no significant difference in mean porosity by scanning electron microscope (SEM) method in MTA+8% nano-silica (31.26±10.73) and MTA (32.74±5.26) (P>0.001). Conclusion: This in vitro study showed us an addition of 8% of nano-silica to MTA reduced the setting time. Although evaluation by imbibition test showed increasing of porosity in nano-silica MTA compared with pure MTA. Keywords: Mineral Trioxide Aggregate; Nano-silica; Porosity; Setting Time